Conferências nacionais de meio ambiente : efetividade e participação social - Ayres, Wilian D'Agostini (2018)
This paper is based on the study about the Brazilian National Environmental Conferences ? CNMA, held in 2003, 2005, 2008, and 2013. Thus, it aims to correlate quantitative and qualitative results from public policies produced after these events, based on legislative proportions derived from them, that is: number of laws, decrees and other legislating devices produced by the conferences, observing the participants profiles and each editions? main theme. Firstly, the historical development of the environmental movement is presented: how it emerged in the international scenario, and its incorporation to the Brazilian agenda, having its basis on the theoretical understanding of public policies and conference methods through indispensable concepts, in order to, then, reach this study?s aim: the legislation generated from the Brazilian National Environmental Conferences, and the social participation in these processes as a way of evaluating the effectiveness of public policies. It is noticed that the administrative profile of the presidents of the republic, Lula and Dilma, changed the methodology of the Conferences, directly impacting the legislative and participatory results